THE PERSISTENCE OF AN ECOLOGICAL SOCIETY: IN-DEPTH CRITICAL ANALYSIS OF THE COMMUNITY MOVEMENT IN GERIANA KAUH, KARANGASEM - Putri, LG. Saraswati (UI Scholars Hub, 2020)
This research investigates the tenacity of the villagers of Geriana Kauh in the Regency of Karangasem, Bali in preserving their culture and nature. Balinese are facing immediate threats due to massive modernization and industrialization. The excessive and intrusive development generated by mega tourism is causing environmental and societal degradations. People from the small village of Geriana Kauh have been striving to protect their ancestral land with the power of cultural consciousness. For the past 10 years, they have been working to rehabilitate their social and ecological crises caused by modernizations. This research utilizes eco-philosophy theories. The first is post-structuralist three ecologies theory by Felix Guattari. Using this critical theory, authors can extract the importance of equilibrium within the psyche, the social, and the ecological. The second is social ecology theory proposed by Murray Bookchin to understand the formation of a conscious ecological society. The novelty of this research is the amalgamation of local wisdom and religious value as progressive tools to create social-ecological transformation. The Balinese foundation of living lies within the philosophy of Tri Hita Karana or three sources of happiness: harmony among one another (pawongan), within the environment (palemahan), and to God (parahyangan). The villagers of Geriana Kauh live by this philosophy. They are predominantly farmers who have inherited land which has been passed down from generation to generation. This farming tradition is also intertwined alongside the ancient tradition of irrigation or Subak. Cultivating lands has become their cultural and spiritual identities.